High performance microspherical activated carbons for methane storage and landfill gas or biogas upgrade - Mestre, Ana S.
Microspherical activated carbons were successfully prepared via a novel synthetic route that involves hydrothermal carbonization of a renewable material, sucrose, and activation with K2CO3. The use of K2CO3 resulted in better yields (similar to 50%) and the retention of the spherical shape of the hydrochar, while with the less environmentally desirable and commonly used activating agent, KOH, the process occurs at the expense of the spherical morphology. The superior performance of the K2CO3 activated samples for methane storage and upgrade of landfill gas or biogas results from the combination of several key properties including high packing densities (similar to 0.9 g cm(-3)), high surface areas (up to 1400 m(2) g(-1)) and micropore sizes suitable for methane storage and selective CO2-CH4 separation. In fact, the micropore size distributions assessed from CO2 adsorption data through a methodology not imposing a Gaussian distribution gave meaningful values to explain both the selectivity and storage capacity of samples. Sample activated with K2CO3 at 800 degrees C presenting micropore sizes similar to 0.8 nm and high packing density has high volumetric methane uptake (90 (V/V) at 1000 kPa), close to the best activated carbons reported in the literature. Sample activated with K2CO3 at 700 degrees C has narrower micropores (similar to 0.5 nm) and presents a remarkable selectivity (4-7) in CO2-CH4 mixtures for the upgrade of methane based fuels, like natural gas, landfill gas, and biogas. Although a superactivated carbon (similar to 2400 m(2) g(-1)) was obtained with KOH activation, the low packing density and wider micropores rendered it less effective for both methane storage and upgrade.